Hubungan Kebiasaan Membaca terhadap Kemampuan Literasi Sains Siswa Kelas VI SDN 8 Singkawang - Septiadi, Fajar; Eka Murdani; Erdi Guna Utama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to 1) describe the reading habits of sixth grade students at SDN 8 Singkawang; 2) describe the scientific literacy skills of sixth grade students at SDN 8 Singkawang; 3) determine the relationship between reading habits and the scientific literacy skills of sixth grade students at SDN 8 Singkawang. The type of research used is quantitative with a correlation design. The population in this study were all sixthgrade students of SDN 8 Singkawang and the sample in this study used Purposive Sampling of 30 students. The data collection techniques for this study were tests and non-tests. The instruments used in this study were test sheets and questionnaires. The data analysis technique used was the Pearson Product Moment correlation test. The results of the study show that 1) Based on the results of the calculation of the questionnaire on students' reading habits, the average value is 71.9%, so it can be concluded that the reading habits of grade VI students of SDN 8 Singkawang have high criteria. 2) Based on the results of the calculation of the scientific literacy ability test questions for grade VI students of SDN 8 Singkawang, the average value is 81.5, so it can be concluded that the scientific literacy ability of students has quite high criteria. 3) Hypothesis testing using obtained t count 0.484> 0.374 t table, so it can be concluded that there is a relationship between reading habits and the scientific literacy ability of grade VI students of SDN 8 Singkawang.